EFFECTS OF CAT CAN THANG COMBINED WITH CERVICAL SPINE EXERCISES ON REDUCING MUSCLE STIFFNESS AND IMPROVING CERVICAL SPINE RANGE OF MOTION IN TREATMENT OF CERVICOBRACHIAL SYNDROM CAUSED BY CERVICAL SPONDYLOSIS (Vietnam Journal of Community Medicine, 2026)
Objectives: Evaluating the effect of Cat can thang combined with cervical spine exercises on reducing muscle stiffness and improving cervical spine range of motion in the treatment of cervicobrachial syndrome caused by cervical spondylosis.Subjects and methods: Clinical intervention research, prospective, comparing before and after treatment. 60 patients in the research group used Cat can thang combined with cervical spine exercises.Results: After 20 days of treatment, the proportion of patients with muscle stiffness decreased from 100% to 21.7%. The post-treatment proportion of patients with muscle stiffness decreased significantly compared to the pre-treatment proportion at all locations (p < 0.05). The average score for restricted cervical spine range of motion decreased from 11.87 ± 3.67 points (moderate restriction) to 3.15 ± 2.18 points (minor restriction). Post-treatment cervical spine range of motion showed a statistically significant increase compared to pre-treatment values (p < 0.05)Conclusion: Cat can thang combined with cervical spine exercises is effective in reducing muscle stiffness and improving cervical spine range of motion in the treatment of cervicobrachial syndrome caused by cervical spondylosis.
Keywords: Cat can thang combined, cervical spine exercises, cervicobrachial syndrome, cervical spondylosis, muscle stiffness, cervical spine range of motion.